2018
DOI: 10.1364/oe.26.003075
|View full text |Cite
|
Sign up to set email alerts
|

Single-photodiode per polarization receiver with signal-signal beat interference suppression through heterodyne detection

Abstract: We show that a simplified, single-photodiode per polarization heterodyne receiver is able to directly suppress signal-signal beat interference (SSBI), without the need for cancellation in the digital domain. We characterize performance degradation due to SSBI, and show that a strong LO in the receiver can mitigate SSBI. Transmission of 400 Gb/s-class signals is shown over single fiber spans of up to 160 km, and over field-deployed metropolitan area fiber. These results indicate that a single photodiode can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…3 (b) presents the SNR with respect to LOSPR at different OSNRs for the receiver without the KK scheme. It can be observed that the increase in SNR with increasing LO power is much more gradual, although at high LOSPR values, effective SSBI suppression is achieved, as described in [17].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…3 (b) presents the SNR with respect to LOSPR at different OSNRs for the receiver without the KK scheme. It can be observed that the increase in SNR with increasing LO power is much more gradual, although at high LOSPR values, effective SSBI suppression is achieved, as described in [17].…”
Section: Resultsmentioning
confidence: 88%
“…The simulations were carried out using MATLAB, with a single channel being considered. The system employed a 28 Gbaud PDM 16-QAM signal, at a gross data rate of 224 Gb/s, encoding a 2 17 de Bruijn binary sequence. Lasers used in the transmitter and receiver were centered at 1550 nm with a linewidth of 1 MHz (unless otherwise stated), typical for the low-cost DFB lasers used in short-reach systems.…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of heterodyne detection with a single photodiode has been investigated in [14]. This provides a saving of one photodiode, but results in signal-signal beating interference (SSBI), in contrast to the case with balanced detection.…”
Section: Reduced-complexity Coherent Receivers For Onusmentioning
confidence: 99%
“…This provides a saving of one photodiode, but results in signal-signal beating interference (SSBI), in contrast to the case with balanced detection. Solutions that have been proposed to overcome this include the use of a high LO-to-signal power ratio, so that the wanted signal-LO beat terms dominate over the signal-signal beat terms [14], and the use of digital signal processing (DSP) to mitigate the SSBI, e.g. the Kramers-Kronig scheme [15][16][17][18].…”
Section: Reduced-complexity Coherent Receivers For Onusmentioning
confidence: 99%